SUSTAINABLE AGRICULTURE- SYSTEM (SAc-S): INOVASI KONSEP PERTANIAN URBAN SEBAGAI PEMBANGUNAN BERKELANJUTAN DAN UPAYA PENANGANAN MASALAH PERKOTAAN - Ula, Mas; Sa’adah, Sa’adah; Amiin, Muhammad Kholiqul (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2014)
Urban development in Indonesia raises some urban problems. One of them is the switch function of agricultural land to residential and industrial. Meanwhile, the food needs of communities dependent on agricultural commodities which in fact require land as a place of production. The concept of urban agriculture emerged as an answer to deal with the problem of urban land and the sustainable development efforts. According to the Farm Bill and Trade Act of 1990, meaning the practice of sustainable agriculture crop production and livestock production systems integrated with certain rules so that it can continue in the long term. Sustainable Agriculture-System (SAc-S) is a proposed solution to address the sustainability of land and food in urban areas as well as a form of sustainable development by looking at the social, economic and environmental. Our idea to realize the urban farm located in one-story building that do not spend the urban land. In addition, the building will be surrounded by several other concepts, namely livestock, fisheries, horticulture and agroforestry. This concept can be applied in the city center to achieve food self-sufficient green city.Keywords: urban land issues, sustainable development, green city